PENGARUH JUS BELIMBING WULUH TERHADAP TEKANAN DARAH PADA PASIEN HIPERTENSI DI WILAYAH KERJA PUSKESMAS ABANG I - Yanti, Ni Kadek Witya Dana; Simanullang, Rostime Hermayerni (STIKes Murni Teguh, 2025)
Hypertension or elevated blood pressure is currently still a health problem in all parts of the world because hypertensive disease is one of the biggest causes of morbidity in the world which significantly increases the risk of heart, brain, and kidney disease, as well as one of the leading causes of premature death worldwide. Objective: The objective of this study is to determine the effect of wuluh starfruit juice on blood pressure in hypertensive patients. Research method is using a pre-experiment type design with a one group pre-posttest design, the sampling technique uses purposive sampling. Wilcoxon signed rank test to analyze the data in this study. The results of this study indicate that there is an effect of wuluh star fruit juice on blood pressure in hypertensive patients in the Puskesmas Abang I Area with a p value of 0.000 and 0.001 or p < 0.05. It is concluded that there is an effect of wuluh star fruit juice on blood pressure. It can be expected that hypertensive patients need to consume star fruit juice because it can lower blood pressure. It is recommended for futher research to add another variable as comparison intervention on blood pressure reduction.